Cytoskeleton Modifications and Autophagy Induction in TCam-2 Seminoma Cells Exposed to Simulated Microgravity. (17th July 2014) - Ferranti, Francesca; Caruso, Maria; Cammarota, Marcella; Masiello, Maria Grazia; Corano Scheri, Katia; Fabrizi, Cinzia; Fumagalli, Lorenzo; Schiraldi, Chiara; Cucina, Alessandra; Catizone, Angela; Ricci, Giulia
Abstract : The study of how mechanical forces may influence cell behavior via cytoskeleton remodeling is a relevant challenge of nowadays that may allow us to define the relationship between mechanics and biochemistry and to address the larger problem of biological complexity. An increasing amount of literature data reported that microgravity condition alters cell architecture as a consequence of cytoskeleton structure modifications. Herein, we are reporting the morphological, cytoskeletal, and behavioral modifications due to the exposition of a seminoma cell line (TCam-2) to simulated microgravity. Even if no differences in cell proliferation and apoptosis were observed after 24 hours of exposure to simulated microgravity, scanning electron microscopy (SEM) analysis revealed that the change of gravity vector significantly affects TCam-2 cell surface morphological appearance. Consistent with this observation, we found that microtubule orientation is altered by microgravity. Moreover, the confocal analysis of actin microfilaments revealed an increase in the cell width induced by the low gravitational force. Microtubules and microfilaments have been related to autophagy modulation and, interestingly, we found a significant autophagic induction in TCam-2 cells exposed to simulated microgravity. This observation is of relevant interest because it shows, for the first time, TCam-2 cell autophagy as a biological response induced by a mechanical stimulus instead of a biochemical one.